Understanding the Structure and Energy Transfer Process of Undoped Ultrathin Emitting Nanolayers Within Interface Exciplexes - Xu, Ting; Fu, Jianhui; Wang, Xinzhong; Lu, Guanhua; Liu, Baiquan (Frontiers in Chemistry, 2022)
Organic light-emitting diodes (OLEDs) have great potential to the display, lighting, and near-infrared (NIR) applications due to their outstanding advantages such as high efficiency, low power consumption, and flexibility. Recently, it is found that ultrathin emitting nano-layer technology plays a key role in OLEDs with simplified structures through the undoped fabricated process and exciplex-forming hosts can enhance the efficiency and stability of OLEDs. However, the elementary structure and mechanism of energy transfer process of ultrathin emitting nano-layer within interface exciplexes is still unclear. Therefore, it is imminently needed to explore the origin of ultrathin emitting nano-layers and its energy process within exciplex. Herein, the mechanism of films grow to firm ultrathin emitting nano-layers (<1 nm) and its energy transfer process within interface exciplexes are reviewed and researched. The UEML phosphorescence dye plays a key role in determining the lifetime of excitons between exciplex or non-exciplex interface. Exciplex between TCTA/Bphen has a longer lifetime decay than that of non-exciplex between TCTA/TAPC, facilitating to excitons harvesting. The findings will be beneficial to not only the further development of OLED but also other related organic optoelectronic technology.